Developing Pedagogical Content Knowledge (PCK) in Pre-Service and In-Service Teacher Training - Hassan bin Sam; Khalid Al-Fansury (Innovative Journal of Educational Research and Insights, 2026)
This study examines the development of Pedagogical Content Knowledge (PCK) in pre-service and in-service teacher training and its impact on teaching effectiveness. Using a qualitative descriptive approach, data were collected through interviews, classroom observations, and document analysis involving teachers and teacher educators. The findings reveal that PCK development significantly enhances teachers’ ability to transform subject matter into meaningful and accessible learning experiences. Pre-service teachers benefit from structured practicum and mentoring, while in-service teachers improve their instructional practices through continuous professional development. The study also highlights the importance of reflective practice, collaboration, assessment, and technology integration in strengthening PCK. However, challenges such as limited resources, time constraints, and varying levels of teacher motivation were identified. The study concludes that a comprehensive and sustained approach to teacher education is essential to optimize PCK development and improve the overall quality of teaching and learning.